St Paul the traveller and the Roman citizen - Ramsay, William Mitchell, Sir, 1851-1939 (London,UK Hodder and Stoughton, 1926)
Includes bibliographical references and indexes.
First published1895. Copy 2 6th ed. 1902, donated by the late Thomas Denton.
Keywords: Paul, the Apostle, Saint -- Biographies